A digital twin-driven approach for the assembly-commissioning of high precision products. (February 2020) - Sun, Xuemin; Bao, Jinsong; Li, Jie; Zhang, Yiming; Liu, Shimin; Zhou, Bin
Highlights: For the HPPs assembly workshops, a theoretical framework for the digital twin-driven assembly-commissioning is developed For the digital twin assembly-commissioning process, an assembly comprehensive factor information model is established The information exchange mechanism between the models is designed through knowledge-based interaction and interoperability interfaces This paper establishes an assembly predictability model and a process optimization model Abstract: High precision products (HPPs) with multidisciplinary coupling are widely used in aerospace, marine, chemical and other fields. Since the internal structure of HPPs is complex and compact, the assembly process requires high precision and involves multidisciplinary coupling. Traditional assembly process of HPPs is based on manual experience, which results in low assembly efficiency and poor-quality consistency. Given the above problems, this research proposes a digital twin-driven assembly-commissioning approach for HPPs. Firstly, this paper introduces the theoretical framework of digital twin-driven assembly-commissioning. Secondly, we introduce the construction method of assembly-commissioning total factor information model based on digital twin technology; the fusion method of twin data and the interoperability method between digital twin models; in addition, the assembliability prediction and assembly-commissioning process optimization methods. Finally, a case study product is used to verify the effectiveness and feasibility of the proposed method.